Sistem Informasi Untuk Posisi Dan Lama Duduk Dengan Smartphone Android Berbasis Mikrokontroler - Era Madona; Muhammad Irmansyah; anggara Nasution (Teknik Elektro Politeknik Negeri Padang, 2018)
In this study, an information system was created to remind users of the length of sitting time to avoid the risk of health problems due to sitting too long. The device is designed and made in two parts, sitting cushion and application on the smartphone. In the seat cushion the limit switch sensor is placed to detect the sitting position and temperature sensor to detect the temperature of the bearing as an indicator of the long sitting. The data detected by the sensor will be sent to the microcontroller and prepared to be sent to the smart phone. The data to be displayed using an android application with Bluetooth communication. Display on the smartphone in human body posture accordance to user's sitting position. There are three body positions, namely the normal position, tilt to the left and tilt to the right. If the body position is tilted, then the smartphone will give an alarm warning to restore the sitting position to the normal position. The bearing temperature detection results will be displayed in the form of numbers with a green background as the indicator of the temperature is still normal, yellow if the bearing temperature rises and red if the temperature has exceeded the permitted normal limit. This means the user has been sitting too long and must stand or rest for a while. To remind the user to stand up, the smartphone will also give a warning by turning on the alarm.